Early childhood caries and its correlation with maternal education level and socio-economic status - Shalu Verma Bhardwaj; Amit Bhardwaj (Wolters Kluwer Medknow Publications, 2014)
Objectives: This study was carried out to correlate the relationship between early childhood caries and maternal education level and socio-economic status (SES). Materials and Methods: The study was conducted on 500 pairs of children of ≤6 years age and their mothers, who reported to the private dental clinic in Gurgaon, Haryana, India. The association between mother's educational level and SES of the family were estimated through a self-structured questionnaire. Caries status of the children was estimated using deft index (World Health Organization criteria). Results: Collected data was statistically analyzed. There was an inverse relationship between the education level of mothers and caries status of their children. There was no relationship between the SES of mothers and caries status of their children. Conclusion: It was concluded that, mothers are responsible for their children primary oral health.